2014
DOI: 10.1155/2014/179705
|View full text |Cite
|
Sign up to set email alerts
|

Anemia Control in Kidney Transplant Recipients Using Once-Monthly Continuous Erythropoietin Receptor Activator: A Prospective, Observational Study

Abstract: In a multicenter, prospective, observational study of 279 kidney transplant recipients with anemia, the efficacy and safety of once-monthly continuous erythropoietin receptor activator (C.E.R.A.) were assessed to a maximum of 15 months. The main efficacy variable was the proportion of patients achieving a hemoglobin level of 11-12 g/dL at each of visits between months 7 and 9. At study entry, 224 patients (80.3%) were receiving erythropoiesis stimulating agent (ESA) therapy including darbepoetin alfa (98), epo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…The only clinically relevant difference detected between immunosuppression regimens was belatacept patients’ increased average hemoglobin range, which may be associated with the increase in average estimated glomerular filtration rate posttransplant seen in belatacept patients compared with patients on calcineurin inhibitors. 36,37 On logistic regression, patients on tacrolimus immunosuppression were also more likely to develop thrombocytopenia and pancytopenia, which persisted on multivariable regression. Although it is possible this is related to residual selection bias between immunosuppression regimens, we have attempted to exclude tacrolimus-treated patients who would not be eligible for belatacept immunosuppression.…”
Section: Discussionmentioning
confidence: 96%
“…The only clinically relevant difference detected between immunosuppression regimens was belatacept patients’ increased average hemoglobin range, which may be associated with the increase in average estimated glomerular filtration rate posttransplant seen in belatacept patients compared with patients on calcineurin inhibitors. 36,37 On logistic regression, patients on tacrolimus immunosuppression were also more likely to develop thrombocytopenia and pancytopenia, which persisted on multivariable regression. Although it is possible this is related to residual selection bias between immunosuppression regimens, we have attempted to exclude tacrolimus-treated patients who would not be eligible for belatacept immunosuppression.…”
Section: Discussionmentioning
confidence: 96%
“…88 Continuous erythropoietin receptor activator therapy also effectively maintained stable hemoglobin levels over 15 months in a real-world study of kidney transplant patients. 89 Similarly, a 1-year study of 77 patients showed stable iron and creatinine levels and a small increase in hemoglobin levels after conversion from short-acting ESAs (epoetin alfa or darbepoetin alfa) to continuous erythropoietin receptor activator therapy at dosages of 50-150 mg/mo. 90…”
Section: Management Of Post-transplant Anemiamentioning
confidence: 96%
“…Hemoglobin, red blood cells, hematocrit and serum iron were higher in the group of kidney transplant recipients than in the group of patients on RRT, and comparable with the group of patients with CKD 3. This is, probably, due to decreasing uremia in most patients after kidney transplantation [2].…”
Section: оригинальные исследованияmentioning
confidence: 99%